Efektivitas Game Edukasi “Transform.It” untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa pada Materi Transformasi Geometri - Dewa Made Wikan Jayanteka Hardika; I Gusti Putu Sudiarta; I Nyoman Budayana (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
This study developed an educational game named Transform.It using the ADDIE development model. The game aims to provide an optimal learning environment to enhance students’ problem-solving skills on the topic of geometric transformations for Grade IX. Transform.It was developed using Construct 3 and underwent validity and practicality evaluations, resulting in an educational game that is feasible for implementation in learning activities. To examine the effectiveness of the game, formative evaluations in the form of pre-tests and post-tests containing problem-solving questions were administered. The results were analyzed using the N-Gain test with a minimum improvement criterion of g ≥ 0.30. The pre-test results showed an average problem-solving score of 33.23, while the post-test results indicated an increase in the average score to 77.38. Based on the N-Gain analysis, Transform.It achieved a gain score of 0.64, which falls within the moderate category and exceeds the minimum criterion. These findings indicate that Transform.It is effective in improving students’ problem-solving skills in geometric transformation material for Grade IX.